On the external forcing of global eruptive activity in the past 300 years - Le Mouël, J-L.; Gibert, D.; Courtillot, V.; Dumont, S.; de Bremond d'Ars, J.; Petrosino, S.; Zuddas, P.; Lopes, F.; Boulé, J-B.; Neves, M. C.; Custódio, S.; Silveira, G.; et al. (Frontiers in Earth Science, 2023)
The decryption of the temporal sequence of volcanic eruptions is a key step in better anticipating future events. Volcanic activity is the results ofrom a complex interaction between internal and external processes, with time scales spanning multiple orders of magnitude. We review periodicities that have been detected or correlated with volcanic eruptions/phenomena and interpreted as resulting from external forces. Taking a global perspective and longer time scales than a few years, we approach this interaction by analyzing three time -series using singular spectral analysis: the global number of volcanic eruptions (NVE) between 1700 and 2022, the number of sunspots (ISSN), a proxy for solar activity, and polar motion (PM) and length of day (lod), two proxies for gravitational force. Several pseudo-periodicities are common to NVE and ISSN, in addition to the 11-year Schwabe cycle that has been reported in previous work, but NVE shares even more periodicities with PM.These quasi-periodic components range from ~5 to ~130 years. We interpret our analytical results in light of the Laplace's paradigm and propose that, similarly to the movement of Earth's rotation axis, global eruptive activity is modulated by commensurable orbital moments of the Jovian planets together with Pluto, whose influence is also detected in solar activity.